Calculation of defect formation energies in UO2. Issue 1645 (2014) - Wiktor, Julia; Vathonne, Emerson; Freyss, Michel; Jomard, Gérald; Bertolus, Marjorie
ABSTRACT: We present a physically justified formalism for the calculation of defect formation energies in UO2. The accessible ranges of chemical potentials of the two components U and O are calculated using the U-O experimental phase diagram and a constraint on the formation energies of vacancies. We then apply this formalism to the DFT+ U investigation of the monovacancies and monointerstitials in UO2 . The results of the most stable charge states of these defects are consistent with a strongly ionic system. Calculations predict similarly low formation energies for $V_U^{4 - }$ and $I_O^{2 - }$ in hyperstoichiometric UO2 .